CONTRIBUTION OF TOURISM INDUSTRY TO LABOR ABSORPTION IN JAMBI CITY - Albetris, Albetris; Nuraini, Nuraini (Dinasti International Journal of Digital Business Management, 2020)
The purpose of this study was to analyze the influence of the contribution of the number of hotels, the number of hotel rooms and tourists to the absorption of labor. Tourism sector is one of the strategic sectors that must be utilized for tourism development as part of national development, having the aim of, among others, expanding business opportunities and opening jobs. The data used in this study is secondary data. The data was obtained from literature related studies in jambi city such as BPS, Department of Culture and Tourism, Youth and Sports, previous research, and other relevant library materials. Data Analysis Method Tested with multiple linear regression models. Based on the results of the study found that Simultaneously independent variable Number of Hotels (X1), Number of Hotel Rooms (X2) and Tourist Visits (X3) affects the variable Absorption of Labor (Y) with a coefficient of determination of 6.5% which means independent variables Number of Hotels (X1), Number of Hotel Rooms (X2) and Tourist Visits (X3) of 6.5% and the remaining 93.5% are influenced by other variables outside this research. And the Number of Hotels had no significant effect on Labor Absorption with a regression coefficient of 0.141